Composite diaphragm, preparation method thereof and secondary battery
Through the coating design of composite particles and polymer particles, the problem of poor electrolyte storage and ion conductivity of existing composite diaphragms when the adhesion is improved is solved, and the adhesion and storage performance of the diaphragm and the electrode sheet are improved, while the ion conductivity is maintained, the cycle performance and energy density of the battery cell are improved, and the increase in the battery cell expansion coefficient is reduced. The battery cell expansion coefficient is small, the capacity retention rate is high, and it has excellent cycle performance and energy density, and the battery cell storage performance and adhesion performance are improved. At the same time, the battery cell storage performance and adhesion performance are improved, and the two-way improvement of the efficient battery cell storage and adhesion performance is achieved.
Patent Information
- Application Number
- CN202511221573.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-29
- Publication Date
- 2025-09-30
- Estimated Expiration
- 2045-08-29
AI Technical Summary
When improving the adhesion between the existing composite diaphragm and the electrode sheet, it is easy to lead to reduced electrolyte storage capacity and poor ion conductivity, affecting the battery's cycle performance and energy density.
The coating design adopts a combination of composite particles and polymer particles. The composite particles include secondary particles formed by the co-agglomeration of first polymer primary particles and ceramics, which are embedded in the filler layer to form protrusions. The polymer particles are located on the surface of the filler layer. Combined with the use of emulsion coating technology, reasonable coverage and embedding depth of the composite particles and polymer particles are ensured.
It improves the bonding performance between the diaphragm and the electrode sheet and the storage space of the electrolyte, maintains the conductivity of the ions, improves the cycle performance and energy density of the battery, and reduces the expansion coefficient of the battery cell and lithium plating phenomenon.
Smart Images

Figure CN120728170A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a composite diaphragm, a preparation method thereof, and a secondary battery. Background Art
[0002] As a portable chemical energy source, batteries are widely used in mobile phones, notebooks, home energy storage, energy storage power stations, new energy vehicles and other fields and industries due to their high energy density, high operating voltage platform, low self-discharge, long service life and environmental friendliness.
[0003] The diaphragm is an important component of the battery. Due to its insulating property that blocks the conduction of electrons, it is designed between the positive and negative electrodes of the battery. The performance of the diaphragm affects the overall performance of the battery. For example, the heat resistance of the diaphragm affects the overall safety of the battery, and the adhesion between the diaphragm and the electrode sheet affects the cycle performance and energy density of the battery. For example, in the Chinese patent application with publication number CN119009359A, a coated diaphragm is designed. An adhesive layer is designed on the inorganic ceramic to improve the adhesion between the diaphragm and the electrode sheet. However, as the adhesion between the diaphragm and the electrode sheet increases, the liquid storage capacity between the diaphragm and the electrode sheet decreases, thereby affecting the overall cycle performance and energy density of the battery; the Chinese patent application with publication number CN1154835A has a design of a coated diaphragm. In the Chinese patent application of 00A, a mixed coating of primary PMMA particles and ceramics is used to obtain a mixed layer of PMMA and ceramics. When the diaphragm and electrode sheets are coated and hot-pressed, the primary PMMA particles can provide storage space for the diaphragm and electrode sheets, effectively improving the battery's liquid storage performance and improving capacity retention. However, as the particle size of the primary PMMA particles increases, the number of bonding sites at the same gram weight decreases, and the bonding between the diaphragm and the electrode sheets weakens. At the same time, as the particle size of the primary PMMA particles increases, the ion conductivity becomes worse, which can easily lead to lithium plating in the battery cell. Therefore, it is necessary to develop a composite diaphragm with a coating to ensure high adhesion between the diaphragm and the electrode sheets while improving the battery's cycle performance and energy density.
[0004] In view of this, the present invention is proposed. Summary of the Invention
[0005] The purpose of the present invention is to provide a composite diaphragm, a preparation method thereof, and a secondary battery. The composite diaphragm provided by the present invention can improve the bonding performance between the diaphragm and the electrode sheet, while having sufficient space for the storage of electrolyte without affecting the conduction of ions. The battery is not prone to lithium deposition, thereby ultimately improving the cycle performance and energy density of the battery.
[0006] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are adopted: A composite diaphragm comprises a base film and a coating disposed on at least one surface of the base film; the coating comprises a first coating disposed on the surface of the base film and a second coating disposed on at least a portion of the surface of the first coating; The first coating layer includes filler particles and composite particles, the filler particles are accumulated to form a filler layer, the composite particles are embedded in the filler layer and form protrusions on the surface of the filler layer; the composite particles include secondary particles formed by the co-agglomeration of first polymer primary particles and ceramics; The second coating layer comprises polymer particles; the polymer particles comprise second polymer primary particles; A height h of the composite particles protruding from the second coating layer satisfies 1 μm≤h≤4.9 μm.
[0007] The method for preparing the composite diaphragm as described above comprises the following steps: Mixing first raw materials to obtain a first mixed slurry, wherein the first raw materials include filler particles and an emulsion containing composite particles; mixing a second raw material to obtain a second mixed slurry, wherein the second raw material includes an emulsion containing polymer particles; The first mixed slurry is applied on at least one side of the base film and dried to obtain a first coating layer; the second mixed slurry is applied on the first coating layer and dried to obtain the composite diaphragm.
[0008] A secondary battery comprises the composite separator described above.
[0009] Compared with the prior art, the present invention has the following beneficial effects: (1) The composite diaphragm provided by the present invention has good air permeability, low internal resistance, is not easy to shed powder, and has good adhesion to the electrode sheet. The ion conductivity of the diaphragm is high and lithium is not easy to be deposited. The battery cell prepared by using the composite diaphragm has a small bulging expansion coefficient, a high capacity retention rate and good cycle performance.
[0010] (2) The composite particles of the present invention include secondary particles formed by the co-agglomeration of the first polymer primary particles and ceramics. Ceramic particles are introduced during the agglomeration process of the primary particles to increase the phase interface between the primary particles in the composite particles, thereby providing more channels for ions, effectively solving the problem of large-particle polymer coating blocking the passage of ions and causing lithium precipitation, thereby improving the cycle performance; in addition, the addition of ceramics to the composite particles increases the affinity between the composite particles and the inorganic filler during coating and slurrying, improves the dispersibility of the slurry system, and makes it difficult for the composite particles to cluster in the composite diaphragm; the addition of ceramics can also effectively increase the relative density of the composite particles. When mixed with filler particles for coating, the composite particles can be effectively embedded in the pores of the filler layer, increasing the adhesion between the composite particles and the coating, thereby solving the problem of powder shedding during the mixed coating of large-particle polymers and inorganic fillers.
[0011] (3) The composite particles of the present invention are used in combination with polymer particles, and the polymer particles are coated on the surface of the first coating layer containing composite particle protrusions, thereby achieving a two-way improvement in the electrolyte storage performance and adhesion performance, while also having good heat resistance; the composite particles are embedded in the filler layer and form protrusions on the surface of the filler layer. When the diaphragm and the electrode sheet are hot-pressed, in addition to providing adhesion, they can also provide spatial points to improve the liquid storage performance of the battery cell, thereby improving the cycle performance of the battery cell; the polymer particles are located on the surface of the filler layer and are not embedded in the filler layer, which can effectively improve the adhesion performance of the composite diaphragm. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] In order to more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the specific embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0013] Figure 1 A schematic structural diagram of a composite diaphragm provided in an embodiment of the present invention; Figure 2 A schematic structural diagram of a first polymer primary particle provided in an embodiment of the present invention; Figure 3 This is a surface SEM image of the composite diaphragm in Example 10 of the present invention; Figure 4 This is a Tg graph of the first polymer primary particles in Example 10 of the present invention; Figure 5 This is a Tg diagram of the polymer particles in Example 10 of the present invention; Figure 6 This is the EDS graph of the composite particles in Example 10 of the present invention.
[0014] Reference numerals: 1-base film; 2-coating layer; 21-first coating layer; 211-composite particles; 212-filling layer; 22-second coating layer; 221-polymer particles; 3-core; 4-shell. DETAILED DESCRIPTION
[0015] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. Those who do not specify specific conditions in the embodiments are carried out according to normal conditions or the conditions recommended by the manufacturer. Those whose reagents or instruments are not specified by the manufacturer are conventional products that can be purchased commercially.
[0016] like Figure 1 As shown, the first aspect of the present invention provides a composite diaphragm, comprising a base film 1 and a coating 2 provided on at least one side of the base film 1; the coating 2 comprises a first coating 21 provided on the surface of the base film 1 and a second coating 22 provided on at least a portion of the surface of the first coating 21; The first coating 21 includes filler particles and composite particles 211. The filler particles are accumulated to form a filler layer 212. The composite particles 211 are embedded in the filler layer 212 and form protrusions on the surface of the filler layer 212. The composite particles 211 include secondary particles formed by the coagulation of the first polymer primary particles and the ceramic. The second coating layer 22 includes polymer particles 221; the polymer particles 221 include second polymer primary particles; The height h of the composite particles protruding from the second coating satisfies 1 μm≤h≤4.9 μm. For example, h can be any value among 1 μm, 2 μm, 3 μm, 4 μm, 4.9 μm, or a range consisting of any two values.
[0017] The present invention uses a compound mixture of composite particles and polymer particles. The composite particles are embedded in the filler layer and form protrusions on the surface of the filler layer. When the diaphragm and the electrode sheet are hot-pressed, in addition to providing adhesion, they can also provide spatial points to improve the liquid storage performance of the battery cell, thereby improving the cycle performance of the battery cell; the polymer particles are located on the surface of the filler layer and are not embedded in the filler layer, which can effectively improve the bonding performance of the composite diaphragm; a two-way improvement in the liquid storage performance and bonding performance of the battery cell is achieved. At the same time, the diaphragm provided by the present invention also has good heat resistance.
[0018] Since the second coating layer is mostly located on the surface of the filler layer, when defining the height of the composite particles protruding from the second coating layer, the second coating layer refers to the second coating layer located on the surface of the filler layer, that is, the height of the second coating layer protruding from the composite particles on the filler layer is 1-4.9 μm; if the protrusion height is too low, the Gap point capacity (height of the spatial site) provided by the composite particles decreases, the liquid storage capacity of the battery cell decreases, the battery cell expansion coefficient increases, and the battery cell performance decreases; if the protrusion height is too high, a larger composite particle size or a smaller embedding depth is required. If the composite particle size is too large, the composite particle coverage rate decreases under the same gram weight, the effective Gap site (number of spatial sites) provided decreases, and when the composite diaphragm and the electrode sheet are hot-pressed, an effective Gap space cannot be provided, which easily leads to an increase in the battery cell expansion coefficient; if the composite particle size is too large or the embedding depth is too small, it is also easy to cause the composite particles to fall off, resulting in reduced adhesion between the composite diaphragm and the electrode sheet, thereby affecting the overall battery cell performance. In some specific embodiments, the test method of h includes: taking a cross-section of the composite diaphragm, measuring the height of multiple composite particles protruding from the second coating layer by photographing a scanning electron microscope, and taking an average value.
[0019] The composite particles used in the present invention include secondary particles formed by the co-agglomeration of first polymer primary particles and ceramics. The introduction of ceramic particles increases the phase interface between the primary particles in the composite particles, thereby providing more channels for ions, and can effectively solve the problem of large-particle polymer coating blocking the passage of ions and causing lithium precipitation, thereby improving the cycle performance; in addition, adding ceramics to the composite particles can also increase the affinity between the composite particles and inorganic fillers during coating and slurrying, thereby improving the dispersibility of the slurry system, and making it difficult for the composite particles to cluster in the composite diaphragm; the addition of ceramics can also effectively increase the relative density of the composite particles. When mixed with filler particles for coating, the composite particles can be effectively embedded in the pores of the filler layer, increasing the adhesion between the composite particles and the coating, thereby solving the problem of powder shedding during the mixed coating of large-particle polymers and inorganic fillers, and improving the adhesion between the composite diaphragm and the electrode.
[0020] The composite diaphragm provided by the present invention has good air permeability, low internal resistance, is not easy to shed powder, and has good adhesion to the electrode sheet. The dry pressing adhesion between the diaphragm and the electrode sheet is greater than 12N / m. The ionic conductivity of the composite diaphragm is greater than 0.9mS / cm, and it is not easy to deposit lithium. The battery cell prepared using the composite diaphragm has a small bulging expansion coefficient, a high capacity retention rate, and excellent cycle stability.
[0021] In some embodiments of the present invention, both the first polymer and the second polymer are non-fluorinated polymers.
[0022] In some specific embodiments of the present invention, the hardness of the composite particles is greater than that of the polymer particles. The polymer particles have a lower hardness, which can effectively improve the bonding performance of the diaphragm to the electrode sheet. The composite particles have a relatively high hardness, which can improve the overall hardness of the battery cell.
[0023] In some specific embodiments of the present invention, the thickness of the filler layer is H, and the depth to which the composite particles are embedded in the filler layer is d, satisfying the following: 1 μm ≤ H ≤ 2 μm, H / 2 ≤ d ≤ H. For example, H can be any value among 1 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, and 2 μm, or a range consisting of any two values; and d can be any value among H / 2, 0.6H, 0.7H, 0.8H, 0.9H, and H, or a range consisting of any two values. Controlling the embedding depth of the composite particles within the above range can ensure adhesion between the composite particles and the coating and avoid powder loss problems caused by mixed coating of large-particle polymer and filler. If the filler layer is too thin or the embedding depth is too shallow, the adhesion between the composite particles and the filler layer is reduced, the composite separator suffers from severe powder loss, and the shedding of the composite particles affects the adhesion between the composite separator and the electrode sheet, resulting in reduced battery cell performance. However, if the filler layer is too thick and the embedding depth is too deep, the protruding height of the composite particles is reduced, affecting the liquid storage performance of the battery cell.
[0024] In some specific embodiments of the present invention, the method for testing d includes: cutting a cross section of the composite diaphragm, measuring the depth of multiple composite particles embedded in the filler layer by photographing with a scanning electron microscope, and taking an average value.
[0025] In some specific embodiments of the present invention, the coverage rate η1 of the composite particles relative to the base film is 4.2%~18.8%, for example, it can be any point value of 4.2%, 5.2%, 5.7%, 6.5%, 7.6%, 8.7%, 9.5%, 11.8%, 12.3%, 14%, 15.6%, 17.3%, and 18.8%, or a range value consisting of any two point values; the coverage rate η2 of the polymer particles relative to the base film is 12.5%~31.7%, for example, it can be any point value of 12.5%, 13.3%, 15%, 18%, 20%, 25%, 30%, and 31.7%, or a range value consisting of any two point values; the total coverage rate η (η=η1+η2) of the first polymer and the second polymer relative to the base film is 25.0%~40.0%, for example, it can be any point value of 25%, 30%, 35%, and 40%, or a range value consisting of any two point values. If η1 is too high or too low, the composite diaphragm air permeability growth rate will increase. At the same time, if η1 is too high, the composite particles are easily piled up, resulting in lithium precipitation. If η1 is too small, the effective spatial sites provided will decrease. When hot-pressed with the pole piece, it cannot provide effective liquid storage space, which will easily lead to an increase in the expansion coefficient of the battery cell. If η2 is too high, the air permeability of the diaphragm will deteriorate. If η2 is too low, the bonding performance will decrease. If both η1 and η2 are high, the total coverage rate η of the polymer particles will be too large, and the air permeability of the diaphragm will deteriorate. If both η1 and η2 are low, the total coverage rate η of the polymer particles will be too small, and the bonding performance will be significantly reduced. Therefore, it is necessary to reasonably control the range of η1, η2 and η. The present invention limits the coverage rate of composite particles and polymer particles and their total coverage rate, so that they can provide sufficient spatial points without deteriorating the permeability of the coating, thereby not affecting the conduction of ions and having high bonding properties.
[0026] In some specific embodiments of the present invention, the testing method of η1 includes: taking a cross-section of the composite diaphragm, measuring the maximum length of multiple composite particles along the coating direction using a scanning electron microscope, taking the average value to obtain the composite particle size L, and calculating the coverage area of a single composite particle according to S=3.14×L×L / 4; taking a composite diaphragm, and testing the number of composite particles per unit area of the diaphragm by photographing with a scanning electron microscope, and calculating the result according to η1=S×the number of composite particles per unit area.
[0027] In some specific embodiments of the present invention, the testing method of η2 includes: taking a composite diaphragm, testing the number of polymer particles per unit area of the diaphragm by shooting with a scanning electron microscope, and calculating it according to η2=(3.14×D2×D2) / 4×the number of polymer particles per unit area, where D2 is the particle size of the polymer particles.
[0028] In some embodiments of the present invention, the surface density of the composite particles is X, and the surface density of the polymer particles is Y, which satisfies: 0.20 g / m2 ≤X≤0.60g / m 2 , Y=-0.125X+a, 0.15≤a≤0.2, for example, X can be 0.20g / m 2 , 0.3g / m 2 , 0.4g / m 2 , 0.5g / m 2 , 0.6g / m 2 Any point value or a range value consisting of any two point values in the range; a can be any point value among 0.15, 0.16, 0.175, 0.19, 0.2 or a range value consisting of any two point values.
[0029] The surface density (coating weight) of the polymer particles decreases as the surface density (coating weight) of the composite particles increases, ensuring that the bonding performance of the composite separator does not deteriorate. The total coverage of the composite particles and polymer particles in the coating does not increase dramatically, thereby not affecting the conduction of ions and ultimately the cycle performance of the battery cell. When the surface density of the composite particles increases, the surface density of the polymer particles also increases, which will lead to an increase in the overall coverage of the composite separator and a significant increase in the air permeability of the separator, affecting the overall internal resistance of the battery cell. At the same time, the gram weight of the composite particles and polymer particles increases, which can easily lead to lithium deposition in the battery cell, thereby affecting the cycle performance of the battery cell. When the surface density of the composite particles decreases, the surface density of the polymer particles also decreases, which will lead to a serious decrease in the adhesion between the composite separator and the electrode sheet, an increase in the battery cell expansion rate, an increase in the internal resistance of the battery cell, and a decrease in the cycle performance of the battery cell.
[0030] In some specific embodiments of the present invention, in the total coating, the ratio K of the number of polymer particles to the number of composite particles satisfies: 11<K<750. For example, K can be any point value among 15, 40, 90, 180, 280, 330, 400, 530, 600, 680, 716, 745 or a range value composed of any two point values.
[0031] In some specific embodiments of the present invention, the testing method of K includes: taking a composite membrane, testing the number of polymer particles and the number of composite particles per unit area of the membrane by shooting with a scanning electron microscope, and calculating the value by the ratio of the number of polymer particles per unit area to the number of composite particles per unit area.
[0032] When the total amount of composite particles and polymer particles is appropriate, if the proportion of composite particles in the composite diaphragm is too high, the polymer particles will be reduced. Since the polymer particles are fully coated with the primary particles, the bonding points they can provide are far more than the composite particles of the secondary particles. Therefore, when bonding with the electrode sheet, the polymer particles contribute more to the adhesion than the composite particles. The reduction of polymer particles will easily lead to a decrease in the bonding strength between the composite diaphragm and the electrode sheet. At the same time, if the proportion of composite particles is too high, it will easily lead to a larger air permeability growth rate of the composite diaphragm, and the composite particles will easily accumulate, leading to lithium precipitation. If the proportion of composite particles is too low, the coverage of polymer particles will increase, and the air permeability growth rate of the composite diaphragm will increase, affecting the internal resistance of the battery cell. At the same time, when the proportion of composite particles is too low, the Gap points (spatial sites) provided will be reduced, and the battery cell expansion coefficient will increase, resulting in a decrease in cycle performance.
[0033] In some specific embodiments of the present invention, the particle size of the composite particles 211 is 4 to 6 μm, for example, it can be any point value among 4 μm, 4.5 μm, 5 μm, 5.5 μm, and 6 μm, or a range value consisting of any two point values; the particle size in the present invention refers to the D50 particle size. The present invention controls the particle size of the composite particles to 4 to 6 μm, which can effectively improve the liquid storage performance of the battery cell, reduce the battery cell expansion coefficient, and ensure the adhesion between the diaphragm and the electrode sheet; if the particle size of the composite particles is too small, the coverage of the composite particles increases under the same gram weight, the air permeability growth rate of the composite diaphragm increases, the internal resistance increases, and in addition After the composite diaphragm and the electrode sheet are hot-pressed, the Gap point capacity (the height of the spatial site) provided by the composite particles decreases, the liquid storage capacity of the battery cell decreases, the battery cell expansion coefficient increases, and the battery cell performance decreases; if the composite particle size is too large, the composite particle coverage rate decreases at the same gram weight, and the effective Gap sites (the number of spatial sites) provided decrease. When the composite diaphragm and the electrode sheet are hot-pressed, an effective Gap space cannot be provided, which can easily lead to an increase in the battery cell expansion coefficient. At the same time, if the composite particle size is too large, it can easily cause the composite particles to fall off, resulting in a decrease in the adhesion between the composite diaphragm and the electrode sheet, thereby affecting the overall battery cell performance.
[0034] In some specific embodiments of the present invention, the particle size of the first polymer primary particles is 0.4~0.6μm, for example, it can be any point value among 0.4μm, 0.45μm, 0.5μm, 0.55μm, 0.6μm or a range value consisting of any two point values; and / or, the observable primary particle size of the ceramic is 0.4~0.6μm, for example, it can be any point value among 0.4μm, 0.45μm, 0.5μm, 0.55μm, 0.6μm or a range value consisting of any two point values.
[0035] In some specific embodiments of the present invention, the mass proportion of ceramics in the composite particles is 5% to 12%. For example, it can be any point value among 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, or a range value consisting of any two point values.
[0036] If the proportion of ceramics in the composite particles is too low or there is no ceramic, when the composite particles are mixed with inorganic fillers (such as inorganic oxides, hydroxides) to form the first slurry, the dispersibility and affinity of the composite particles and the fillers are weakened, the composite particles are easily accumulated in the composite diaphragm, and the ion conduction channel of the composite particles is reduced, which can easily lead to lithium precipitation in the battery cell. At the same time, the depth of the composite particles embedded in the filler layer is insufficient, the adhesion between the composite particles and the filler layer is reduced, the composite diaphragm sheds powder seriously, and the composite particles fall off, affecting the adhesion between the composite diaphragm and the electrode sheet, and the battery cell performance is reduced; if the proportion of ceramics in the composite particles is too high, under the same gram weight, the adhesion between the composite particles and the electrode sheet is reduced, resulting in an increase in the interface resistance between the diaphragm and the electrode sheet, a decrease in cycle performance, too low adhesion, a decrease in the battery cell hardness, and a more likely expansion of the battery cell.
[0037] In some specific embodiments of the present invention, the ceramic used to form the composite particles includes at least one of boehmite, alumina, silica, zirconia, LATP, and LLZO.
[0038] In some specific embodiments of the present invention, the ceramic forming the composite particles is a ceramic modified by a coupling agent, the purpose of which is to improve the co-agglomeration effect of the ceramic and the first polymer primary particles.
[0039] In some specific embodiments of the present invention, the glass transition temperature Tg of the first polymer primary particles is -5~5°C, for example, it can be any point value among -5°C, -3°C, -1°C, 0°C, 2°C, 5°C, or a range value consisting of any two point values.
[0040] In some specific embodiments of the present invention, Figure 2 As shown, the first polymer primary particle includes a core 3 and a shell 4 coated on the surface of the core 3; the core monomer forming the core 3 and the shell monomer forming the shell 4 are independently selected from at least one of methacrylonitrile, styrene, acrylonitrile, ethyl acrylate, 1-butene, 2-ethylhexyl acrylate, isooctyl acrylate, and n-butyl acrylate; and the shell monomer contains at least one monomer different from the core monomer.
[0041] In some preferred embodiments of the present invention, the molecular chain of the core includes a first structural unit, and the molecular chain of the shell includes a first structural unit and a second structural unit. The monomer forming the first structural unit includes at least one of methacrylonitrile, styrene, and acrylonitrile, and the monomer forming the second structural unit includes at least one of ethyl acrylate, 2-ethylhexyl acrylate, isooctyl acrylate, and n-butyl acrylate. By regulating the types of monomers that make up the core-shell structure, the core-shell structure has the characteristics of being soft on the outside and hard on the inside, which not only improves adhesion to the electrode sheet but also increases the overall hardness of the battery cell.
[0042] In some specific embodiments of the present invention, the particle size of the polymer particles 221 is 0.6-1.0 μm, for example, any value among 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, or a range consisting of any two values.
[0043] In some specific embodiments of the present invention, the glass transition temperature Tg of the polymer particles is 45-55°C, for example, it can be any point value among 45°C, 48°C, 50°C, 52°C, 55°C, or a range consisting of any two points.
[0044] In some specific embodiments of the present invention, the monomers forming the second polymer include any two of methyl methacrylate, butyl methacrylate, ethyl acrylate, isooctyl acrylate, and n-butyl acrylate.
[0045] In some specific embodiments of the present invention, the mass proportion of the composite particles in the total coating is 11.5% to 18.5%. For example, it can be any point value among 11.5%, 13%, 14%, 15%, 16%, 17%, 18.5%, or a range value consisting of any two point values.
[0046] In some specific embodiments of the present invention, the mass proportion of polymer particles in the total coating is 3.0% to 9.0%, for example, it can be any point value among 3.0%, 5.0%, 7.0%, 9.0% or a range value consisting of any two point values.
[0047] In some specific embodiments of the present invention, the mass proportion of filler particles in the total coating is 66% to 86%, for example, it can be any point value among 66%, 70%, 75%, 80%, 86% or a range value consisting of any two point values.
[0048] In some embodiments of the present invention, the filler particles include one or more of inorganic oxides, inorganic hydroxides, metal salts, or organic non-polymer particles. For example, the filler particles may include at least one of boehmite, aluminum oxide, magnesium hydroxide, tin dioxide, silicon dioxide, barium sulfate, LLZO, LATP, and melamine cyanurate.
[0049] In some specific embodiments of the present invention, the particle size of the filler particles is 0.5-0.8 μm, for example, any value among 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, or a range consisting of any two values.
[0050] In some specific embodiments of the present invention, more than 95% of the second coating is located on the surface of the filler layer. This is because the coverage of the composite particles is lower than that of the filler layer, and since the composite particles protrude from the surface of the filler layer, the slurry coated on the surface of the composite particles is prone to slide due to gravity. Therefore, most of the second coating is located on the surface of the filler layer.
[0051] In some specific embodiments of the present invention, the first coating layer further contains a first binder, and the mass proportion of the first binder in the total coating layer is 2% to 8%, for example, it can be any point value among 2%, 4%, 6%, and 8%, or a range value consisting of any two point values; and / or, the second coating layer further contains a second binder, and the mass proportion of the second binder in the total coating layer is 0.05% to 0.50%, for example, it can be any point value among 0.05%, 0.10%, 0.30%, and 0.50%, or a range value consisting of any two point values.
[0052] In some specific embodiments of the present invention, the first binder and the second binder are independently selected from at least one of epoxy resin, styrene-butadiene rubber, polyacrylate, polyamide, polystyrene, and polyvinyl alcohol.
[0053] In some specific embodiments of the present invention, the first coating layer further contains a first wetting agent, and the mass proportion of the first wetting agent in the total coating layer is 0.1% to 1.0%, for example, it can be any point value among 0.1%, 0.3%, 0.5%, 0.8%, 1.0%, or a range value consisting of any two point values; and / or, the second coating layer further contains a second wetting agent, and the mass proportion of the second wetting agent in the total coating layer is 0.02% to 0.2%, for example, it can be any point value among 0.02%, 0.05%, 0.1%, 0.15%, 0.2%, or a range value consisting of any two point values.
[0054] In some specific embodiments of the present invention, the first wetting agent and the second wetting agent are independently selected from at least one of alkylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, fatty acid polyoxyethylene ether, polyoxyethylene fatty alcohol ether, polyoxyethylene polyoxypropylene block copolymer, and polyoxyethylene alkylphenol ether.
[0055] In some specific embodiments of the present invention, the base film includes any one of a single-layer PP porous film, a single-layer PE porous film, a double-layer PE / PP composite film, and a double-layer PP / PP composite film.
[0056] In some specific embodiments of the present invention, the thickness of the base film is 5 to 16 μm, for example, it can be any value among 5 μm, 8 μm, 10 μm, 12 μm, 16 μm, or a range consisting of any two values.
[0057] A second aspect of the present invention provides a method for preparing the composite diaphragm according to any one of the aforementioned embodiments, comprising the following steps: Mixing first raw materials to obtain a first mixed slurry, the first raw materials including filler particles and an emulsion containing composite particles; mixing a second raw material to obtain a second mixed slurry, wherein the second raw material includes an emulsion containing polymer particles; The first mixed slurry is coated on at least one side surface of the base film and dried to obtain a first coating layer; the second mixed slurry is then coated on the first coating layer and dried to obtain a composite diaphragm.
[0058] The method of the present invention mixes filler particles and composite particles into a slurry and applies it to the surface of the base film to form a first coating layer, which can form a filler layer on the base film, and at the same time embed the composite particles in the filler layer and form protrusions on the surface of the filler layer. When the diaphragm and the electrode sheet are hot-pressed, in addition to providing adhesion, it can also provide spatial points to improve the liquid storage performance of the battery cell, thereby improving the cycle performance of the battery cell; coating polymer particles on the surface of the first coating layer can effectively improve the adhesion performance between the composite diaphragm and the electrode sheet, and at the same time, the composite coating obtained by this method has better heat resistance; and the preparation process of the method of the present invention is simple and easy to implement.
[0059] In some embodiments of the present invention, the method for preparing an emulsion containing composite particles comprises the following steps: S1. A first emulsifier, a core monomer, and a first initiator are subjected to a first polymerization reaction in a first solvent to obtain a core particle emulsion; the core particle emulsion is subjected to UV irradiation, a shell monomer and a second initiator are added to carry out a second polymerization reaction to obtain an emulsion containing a first polymer primary particle; S2. Modify the ceramic surface by reacting the ceramic with a coupling agent to improve the bonding degree and uniformity between the ceramic and the first polymer primary particles. Then, add the emulsion containing the first polymer primary particles and salt and stir to obtain an emulsion containing composite particles.
[0060] The present invention adopts an emulsion demulsification method to agglomerate primary particles into secondary particles. Ceramic particles are added during the agglomeration process to increase the phase interface between the primary particles in the composite particles, thereby providing more channels for ions, effectively solving the problem of large-particle polymer coating blocking the passage of ions and causing lithium precipitation, thereby improving the cycle performance; in addition, the addition of ceramics can also improve the dispersibility of the slurry system, while increasing the relative density of the composite particles, so that they are effectively embedded in the gaps of the filler layer, and increase the adhesion between the composite particles and the coating.
[0061] In some embodiments of the present invention, the UV irradiation conditions are: using a wavelength of 320nm~400nm, an energy of 200mJ / cm 2 ~280mJ / cm 2 The UV light can be irradiated for 1.5h~2.5h. For example, the wavelength can be any point value among 320nm, 340nm, 360nm, 380nm, 400nm or a range of any two point values; the energy can be 200mJ / cm 2 , 220mJ / cm 2 、240mJ / cm 2 , 260mJ / cm 2 、280mJ / cm 2 any point value in the range or any two point values; the irradiation time can be any point value in the range of 1.5h, 1.8h, 2h, 2.2h, 2.5h or any two point values.
[0062] In some specific embodiments of the present invention, in step S2, the mass ratio of the ceramic to the first polymer primary particles is 5:95~12:88, for example, it can be any point value among 5:95, 8:92, 10:90, 12:88 or a range value consisting of any two point values.
[0063] In some specific embodiments of the present invention, in step S2, the stirring speed is 100~200 rpm, for example, it can be any point value among 100 rpm, 120 rpm, 150 rpm, 180 rpm, 200 rpm, or a range value consisting of any two point values; the stirring time is 6~10 h, for example, it can be any point value among 6 h, 7 h, 8 h, 9 h, 10 h, or a range value consisting of any two point values.
[0064] In some specific embodiments of the present invention, in step S2, the coupling agent includes but is not limited to at least one of vinyltriethoxysilane, γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, and γ-methacryloxypropyltrimethoxysilane.
[0065] In some specific embodiments of the present invention, in step S2, the salt used includes but is not limited to sodium sulfate. As an example, sodium sulfate can be added in the form of a solution.
[0066] In some embodiments of the present invention, the first emulsifier includes but is not limited to sodium lauryl sulfate.
[0067] In some embodiments of the present invention, the first initiator and the second initiator are independently selected from persulfates, such as potassium persulfate or sodium persulfate.
[0068] In some embodiments of the present invention, the method for preparing an emulsion containing polymer particles comprises the following steps: The second emulsifier, the monomer for forming the second polymer and the third initiator are subjected to a third polymerization reaction in the second solvent to obtain an emulsion containing polymer particles.
[0069] In some embodiments of the present invention, the second emulsifier includes but is not limited to sodium lauryl sulfate.
[0070] In some embodiments of the present invention, the third initiator includes but is not limited to potassium persulfate.
[0071] In some specific embodiments of the present invention, the first raw material further includes a first binder and / or a first wetting agent.
[0072] In some specific embodiments of the present invention, the second raw material further includes a second binder and / or a second wetting agent.
[0073] A third aspect of the present invention provides a secondary battery comprising the composite diaphragm according to any one of the aforementioned embodiments, or a composite diaphragm produced by the method for producing the composite diaphragm according to any one of the aforementioned embodiments.
[0074] The following describes some embodiments of the present invention in detail with reference to specific application examples. Unless otherwise specified, the raw materials used in the examples can be purchased from the market.
[0075] Example 1 The present embodiment provides a composite diaphragm, comprising a PE base film with a thickness of 7 μm and a coating arranged on one surface of the base film, wherein the coating comprises a first coating arranged on the base film and a second coating arranged on at least a portion of the surface of the first coating, and more than 95% of the second coating is located on the surface of the filler layer; the first coating comprises composite particles, filler particles (aluminum oxide with a particle size of 0.6 μm), a first binder and a first wetting agent, and the second coating comprises polymer particles, a second binder and a second wetting agent, both of which are styrene-butadiene rubber, and both of which are alkylphenol polyoxyethylene ethers; the total coating consisting of the first coating and the second coating comprises, by mass percentage, 12.92% composite particles, 4.14% polymer particles, 78.92% filler particles, 3.35% first binder, 0.14% second binder, 0.48% first wetting agent, and 0.05% second wetting agent; wherein the coating gram weight (surface density) of the composite particles is 0.38 g / m 2 The coating weight (area density) of the polymer particles is 0.122 g / m 2 .
[0076] The preparation method is as follows: (1) Preparation of the first polymer primary particle emulsion: 140 parts of deionized water and 0.5 parts of sodium lauryl sulfate were added to the reactor and stirred evenly. Nitrogen was introduced to expel the air in the reactor. 15 parts of acrylonitrile core monomer were added. The pH of the reaction was adjusted to 7.0-8.0 with 0.01 mol / L acetic acid. The reaction was heated to 85°C and pressurized to 2 MPa. 0.3 parts of potassium persulfate were added and the reaction was carried out for 4 h to obtain the core particle emulsion. The core particle emulsion was subjected to UV irradiation (using a wavelength of 360 nm and an energy of 240 mJ / cm 2 and irradiating with ultraviolet light for 2 hours), then adding 12 parts of acrylonitrile, 33 parts of 2-ethylhexyl acrylate shell monomer, and 0.6 parts of potassium persulfate, adjusting the temperature to 76° C., adjusting the pressure to 4 MPa, reacting for 8 hours, and then cooling and reducing the pressure to room temperature and pressure to obtain a first polymer primary particle emulsion; (2) Preparation of composite particles: 7.0 parts of boehmite with a particle size of 0.5 μm, 0.08 parts of vinyltriethoxysilane and 30 parts of deionized water were added to a reactor, heated to 80°C, pressurized to 3 MPa, and the ceramic surface was modified. The temperature and pressure were then lowered to room temperature and pressure, and 200 parts of the first polymer primary particle emulsion were added, and 0.3 parts of 0.5 mol / L sodium sulfate were added. The mixture was stirred at 150 rpm for 8 h to obtain composite particles. The mixture was diluted with water to a solid content of 20% to obtain an emulsion containing composite particles. (3) Preparation of polymer particles: 160 parts of deionized water and 0.4 parts of sodium lauryl sulfate were added to a reactor and stirred evenly. Nitrogen was introduced to expel the air in the reactor. 19 parts of methyl methacrylate and 21 parts of ethyl acrylate were added. The pH of the reaction was adjusted to 7-8. The reaction mixture was heated to 78°C and pressurized to 2.5 MPa. 0.6 parts of potassium persulfate were added and reacted for 6 h. The temperature and pressure were then lowered to room temperature and pressure. Water was added to dilute the mixture to a solid content of 15% to obtain an emulsion containing polymer particles. (4) Preparation of a first mixed slurry: 82.5 parts of alumina with a particle size of 0.6 μm, 67.5 parts of the emulsion containing composite particles prepared in step (2), 3.5 parts of styrene-butadiene rubber, 0.5 parts of alkylphenol polyoxyethylene ether and 300 parts of deionized water were mixed and stirred to obtain a first mixed slurry; (5) Preparation of a second mixed slurry: 60 parts of the emulsion containing polymer particles prepared in step (3), 0.3 parts of styrene-butadiene rubber, 0.1 parts of alkylphenol polyoxyethylene ether and 140 parts of deionized water were mixed and stirred to obtain a second mixed slurry; (6) Preparation of composite diaphragm: Take the first mixed slurry, use micro-gravure coating technology, adjust the micro-gravure coating speed ratio to 1.20, coat the first mixed slurry on the base film, dry it, and obtain a surface density of 2.82g / m 2 Then take the second mixed slurry, also using micro-gravure coating technology, adjust the micro-gravure coating speed ratio to 1.15, the second mixed slurry is coated on the first coating, dried, control the second coating surface density of 0.13g / m 2 , and obtain a composite diaphragm.
[0077] Example 2 The structure of the composite diaphragm in this embodiment is similar to that in embodiment 1, except that: The total coating composed of the first coating and the second coating is composed of the following by mass percentage: composite particles 14.32%, polymer particles 4.35%, filler particles 77.30%, first binder 3.35%, second binder 0.15%, first wetting agent 0.48%, second wetting agent 0.05%; wherein, the coating weight of the composite particles is 0.40g / m 2 The coating weight of the polymer particles is 0.120 g / m 2 ; The differences in other parameters are shown in Table 1 and Table 2.
[0078] The preparation method is similar to that of the composite membrane in Example 1, except that: In step (1), the core reaction temperature is 85.5°C, the pressure is 2.2 MPa, the shell monomers acrylonitrile and 2-ethylhexyl acrylate are added in amounts of 10 parts and 35 parts, respectively, the reaction temperature is 76°C, and the pressure is 4.3 MPa; In step (2), the amount of boehmite added was 7.6 parts, and the stirring speed was 180 rpm; In step (3), the amounts of methyl methacrylate and ethyl acrylate added were 20 parts and 20 parts respectively, the reaction temperature was 78.5°C, and the pressure was 2.6 MPa; In step (4), the amount of aluminum oxide added is 81 parts, and the amount of the emulsion containing composite particles added is 75 parts; In step (6), the surface density of the first coating is 2.64 g / m 2 , the surface density of the second coating is 0.13g / m 2 .
[0079] Example 3 The structure of the composite diaphragm in this embodiment is similar to that in embodiment 1, except that: The total coating composed of the first coating and the second coating is composed of the following by mass percentage: composite particles 15.33%, polymer particles 6.82%, filler particles 73.81%, first binder 3.26%, second binder 0.23%, first wetting agent 0.47%, second wetting agent 0.08%; wherein, the coating weight of the composite particles is 0.30g / m 2 The coating weight of the polymer particles is 0.132 g / m 2 ; The differences in other parameters are shown in Table 1 and Table 2.
[0080] The preparation method is similar to that of the composite membrane in Example 1, except that: In step (1), the core reaction temperature is 84.5°C, the pressure is 2.1 MPa, the shell monomers acrylonitrile and 2-ethylhexyl acrylate are added in amounts of 11 parts and 34 parts, respectively, the reaction temperature is 76.5°C, and the pressure is 4.2 MPa; In step (2), the amount of boehmite added was 3.5 parts, and the stirring speed was 145 rpm; In step (3), the amounts of methyl methacrylate and ethyl acrylate added were 22 parts and 18 parts, respectively, the reaction temperature was 79.0°C, and the pressure was 2.4 MPa; In step (4), the amount of aluminum oxide added is 79.5 parts, and the amount of the emulsion containing the composite particles added is 82.5 parts; In step (6), the surface density of the first coating is 1.80 g / m 2 The surface density of the second coating is 0.14g / m 2 .
[0081] Example 4 The structure of the composite diaphragm in this embodiment is similar to that in embodiment 1, except that: The total coating composition of the first coating and the second coating is as follows: 17.43% composite particles, 3.05% polymer particles, 75.49% filler particles, 3.39% first binder, 0.11% second binder, 0.49% first wetting agent, and 0.04% second wetting agent. The coating weight of the composite particles is 0.57 g / m 2 The coating weight of the polymer particles is 0.099g / m 2 ; The differences in other parameters are shown in Table 1 and Table 2.
[0082] The preparation method is similar to that of the composite membrane in Example 1, except that: In step (1), the core reaction temperature is 85.8°C, the pressure is 2.4 MPa, the shell monomers acrylonitrile and 2-ethylhexyl acrylate are added in amounts of 8 parts and 37 parts respectively, the reaction temperature is 76.6°C, and the pressure is 4.2 MPa; In step (2), the amount of boehmite added was 6.9 parts, and the stirring speed was 140 rpm; In step (3), the amounts of methyl methacrylate and ethyl acrylate added were 21 parts and 19 parts, respectively, the reaction temperature was 77.5°C, and the pressure was 2.4 MPa; In step (4), the amount of aluminum oxide added is 78 parts, and the amount of the emulsion containing the composite particles added is 90 parts; In step (6), the surface density of the first coating is 3.16 g / m 2 , the surface density of the second coating is 0.10g / m 2 .
[0083] Example 5 The structure of the composite diaphragm in this embodiment is similar to that in embodiment 1, except that: The total coating composed of the first coating and the second coating is composed of the following components by mass percentage: composite particles 11.98%, polymer particles 7.55%, filler particles 76.42%, first binder 3.23%, second binder 0.26%, first wetting agent 0.47%, second wetting agent 0.09%; wherein, the coating weight of the composite particles is 0.22g / m 2 The coating weight of the polymer particles is 0.141 g / m 2 ; The differences in other parameters are shown in Table 1 and Table 2.
[0084] The preparation method is similar to that of the composite membrane in Example 1, except that: In step (1), the core reaction temperature is 86.2°C, the pressure is 2.1 MPa, the shell monomers acrylonitrile and 2-ethylhexyl acrylate are added in amounts of 11 parts and 34 parts, respectively, the reaction temperature is 75.8°C, and the pressure is 3.9 MPa; In step (2), the amount of boehmite added was 7.7 parts, and the stirring speed was 170 rpm; In step (3), the amounts of methyl methacrylate and ethyl acrylate added were 19.5 parts and 20.5 parts, respectively, the reaction temperature was 78.0°C, and the pressure was 2.3 MPa; In step (4), the amount of aluminum oxide added is 83 parts, and the amount of the emulsion containing the composite particles added is 65 parts; In step (6), the surface density of the first coating is 1.72 g / m 2 , the surface density of the second coating is 0.15g / m 2 .
[0085] Example 6 The structure of the composite diaphragm in this embodiment is similar to that in embodiment 1, except that: The total coating composed of the first coating and the second coating is composed of the following by mass percentage: composite particles 12.47%, polymer particles 7.35%, filler particles 76.13%, first binder 3.24%, second binder 0.25%, first wetting agent 0.47%, second wetting agent 0.09%; wherein, the coating weight of the composite particles is 0.24g / m 2 The coating weight of the polymer particles is 0.139 g / m 2 ; The differences in other parameters are shown in Table 1 and Table 2.
[0086] The preparation method is similar to that of the composite membrane in Example 1, except that: In step (1), the core reaction temperature is 84.8°C, the pressure is 1.9 MPa, the shell monomers acrylonitrile and 2-ethylhexyl acrylate are added in amounts of 12 parts and 33 parts, respectively, the reaction temperature is 74.8°C, and the pressure is 4.1 MPa; In step (2), the amount of boehmite added was 6.4 parts, and the stirring speed was 140 rpm; In step (3), the amounts of methyl methacrylate and ethyl acrylate added were 18.5 parts and 21.5 parts, respectively, the reaction temperature was 78.6°C, and the pressure was 2.4 MPa; In step (4), the amount of aluminum oxide added is 82.5 parts, and the amount of the emulsion containing the composite particles added is 67.5 parts; In step (6), the surface density of the first coating is 1.75 g / m 2 , the surface density of the second coating is 0.15g / m 2 .
[0087] Example 7 The structure of the composite diaphragm in this embodiment is similar to that in embodiment 1, except that: The total coating composed of the first coating and the second coating is composed of the following by mass percentage: composite particles 13.76%, polymer particles 4.93%, filler particles 77.27%, first binder 3.33%, second binder 0.17%, first wetting agent 0.48%, second wetting agent 0.06%; wherein, the coating weight of the composite particles is 0.35g / m 2 The coating weight of the polymer particles is 0.126 g / m 2 ; The differences in other parameters are shown in Table 1 and Table 2.
[0088] The preparation method is similar to that of the composite membrane in Example 1, except that: In step (1), the core reaction temperature is 83.8°C, the pressure is 1.7 MPa, the shell monomers acrylonitrile and 2-ethylhexyl acrylate are added in amounts of 12 parts and 33 parts, respectively, the reaction temperature is 75.8°C, and the pressure is 3.9 MPa; In step (2), the amount of boehmite added was 5.8 parts, and the stirring speed was 142 rpm; In step (3), the amounts of methyl methacrylate and ethyl acrylate added were 20.0 parts and 20.0 parts, respectively, the reaction temperature was 76.6°C, and the pressure was 2.8 MPa; In step (4), the amount of aluminum oxide added is 81.5 parts, and the amount of the emulsion containing composite particles added is 72.5 parts; In step (6), the surface density of the first coating is 2.42 g / m 2 , the surface density of the second coating is 0.13g / m 2 .
[0089] Example 8 The structure of the composite diaphragm in this embodiment is similar to that in embodiment 1, except that: The total coating composed of the first coating and the second coating is composed of the following by mass percentage: composite particles 11.90%, polymer particles 8.16%, filler particles 75.89%, first binder 3.21%, second binder 0.28%, first wetting agent 0.46%, second wetting agent 0.10%; wherein, the coating weight of the composite particles is 0.21g / m 2 The coating weight of the polymer particles is 0.143 g / m 2 ; The differences in other parameters are shown in Table 1 and Table 2.
[0090] The preparation method is similar to that of the composite membrane in Example 1, except that: In step (1), the core reaction temperature is 86.8°C, the pressure is 2.1 MPa, the shell monomers acrylonitrile and 2-ethylhexyl acrylate are added in amounts of 10 parts and 35 parts, respectively, the reaction temperature is 76.8°C, and the pressure is 4.3 MPa; In step (2), the amount of boehmite added was 4.9 parts, and the stirring speed was 135 rpm; In step (3), the amounts of methyl methacrylate and ethyl acrylate added were 20.0 parts and 20.0 parts, respectively, the reaction temperature was 79.6°C, and the pressure was 2.6 MPa; In step (4), the amount of aluminum oxide added is 83 parts, and the amount of the emulsion containing the composite particles added is 65 parts; In step (6), the surface density of the first coating is 1.60 g / m 2 , the surface density of the second coating is 0.15g / m 2 .
[0091] Example 9 The structure of the composite diaphragm in this embodiment is similar to that in embodiment 1, except that: The total coating composed of the first coating and the second coating is composed of the following by mass percentage: composite particles 17.92%, polymer particles 3.04%, filler particles 75.02%, first binder 3.39%, second binder 0.11%, first wetting agent 0.48%, second wetting agent 0.04%; wherein, the coating weight of the composite particles is 0.58g / m 2 The coating weight of the polymer particles is 0.098g / m 2 ; The differences in other parameters are shown in Table 1 and Table 2.
[0092] The preparation method is similar to that of the composite membrane in Example 1, except that: In step (1), the core reaction temperature is 83.6°C, the pressure is 2.3 MPa, the shell monomers acrylonitrile and 2-ethylhexyl acrylate are added in amounts of 7 parts and 38 parts respectively, the reaction temperature is 74.8°C, and the pressure is 4.1 MPa; In step (2), the amount of boehmite added was 3.8 parts, and the stirring speed was 180 rpm; In step (3), the amounts of methyl methacrylate and ethyl acrylate added were 19 parts and 21 parts, respectively, the reaction temperature was 77.7°C, and the pressure was 2.3 MPa; In step (4), the amount of aluminum oxide added is 77.5 parts, and the amount of the emulsion containing the composite particles added is 92.5 parts; In step (6), the surface density of the first coating is 3.14 g / m 2 , the surface density of the second coating is 0.10g / m 2 .
[0093] Example 10 The structure of the composite diaphragm in this embodiment is similar to that in embodiment 1, except that: The total coating composed of the first coating and the second coating is composed of the following by mass percentage: composite particles 17.10%, polymer particles 4.83%, filler particles 74.03%, first binder 3.33%, second binder 0.17%, first wetting agent 0.48%, second wetting agent 0.06%; wherein, the coating weight of the composite particles is 0.41g / m 2 The coating weight of the polymer particles is 0.115 g / m 2 ; The differences in other parameters are shown in Table 1 and Table 2.
[0094] The preparation method is similar to that of the composite membrane in Example 1, except that: In step (1), the core reaction temperature is 84.6°C, the pressure is 2.2 MPa, the shell monomers acrylonitrile and 2-ethylhexyl acrylate are added in amounts of 11 parts and 13 parts, respectively, the reaction temperature is 75.8°C, and the pressure is 4.0 MPa; In step (2), the amount of boehmite added was adjusted to 7.9 parts and the stirring speed was adjusted to 155 rpm; In step (3), the amounts of methyl methacrylate and ethyl acrylate added were 20 parts and 20 parts respectively, the reaction temperature was 78.7°C, and the pressure was 2.4 MPa; In step (4), the amount of aluminum oxide added is 78 parts, and the amount of the emulsion containing the composite particles added is 90 parts; In step (6), the surface density of the first coating is 2.27 g / m 2 , the surface density of the second coating is 0.12g / m 2 .
[0095] Comparative Example 1 This comparative example refers to the preparation method of the composite diaphragm in Example 1, except that: In step (1), the core reaction temperature is 85.6°C, the pressure is 2.3 MPa, the shell monomers acrylonitrile and 2-ethylhexyl acrylate are added in amounts of 8 parts and 37 parts respectively, the reaction temperature is 73.3°C, and the pressure is 4.4 MPa; In step (2), the amount of boehmite added was adjusted to 1.2 parts and the stirring speed was adjusted to 170 rpm; In step (3), the amounts of methyl methacrylate and ethyl acrylate added were 21 parts and 19 parts, respectively, the reaction temperature was 76.7°C, and the pressure was 2.7 MPa; In step (4), the amount of aluminum oxide added is 79.5 parts, and the amount of the emulsion containing the composite particles added is 82.5 parts; In step (6), the surface density of the first coating is 2.68 g / m 2 , the surface density of the second coating is 0.12g / m 2 .
[0096] Comparative Example 2 This comparative example refers to the preparation method of the composite diaphragm in Example 1, except that: In step (1), the core reaction temperature is 82.6°C, the pressure is 2.4 MPa, the shell monomers acrylonitrile and 2-ethylhexyl acrylate are added in amounts of 8 parts and 37 parts respectively, the reaction temperature is 76.2°C, and the pressure is 3.8 MPa; In step (2), the amount of boehmite added was 10.6 parts, and the stirring speed was 165 rpm; In step (3), the amounts of methyl methacrylate and ethyl acrylate added were 20 parts and 20 parts respectively, the reaction temperature was 77.0°C, and the pressure was 2.3 MPa; In step (4), the amount of aluminum oxide added is 78 parts, and the amount of the emulsion containing the composite particles added is 90 parts; In step (6), the surface density of the first coating is 2.84 g / m 2 , the surface density of the second coating is 0.11g / m 2 .
[0097] Comparative Example 3 This comparative example refers to the preparation method of the composite diaphragm in Example 1, except that: In step (1), the core reaction temperature is 83.9°C, the pressure is 1.9 MPa, the shell monomers acrylonitrile and 2-ethylhexyl acrylate are added in amounts of 10 parts and 35 parts, respectively, the reaction temperature is 74.3°C, and the pressure is 4.2 MPa; In step (2), the amount of boehmite added was 0 parts, and the stirring speed was 170 rpm; In step (3), the amounts of methyl methacrylate and ethyl acrylate added were 20 parts and 20 parts respectively, the reaction temperature was 78.7°C, and the pressure was 2.8 MPa; In step (4), the amount of aluminum oxide added is 79 parts, and the amount of the emulsion containing the composite particles added is 85 parts; In step (6), the surface density of the first coating is 2.60 g / m 2 , the surface density of the second coating is 0.12g / m 2 .
[0098] Comparative Example 4 This comparative example refers to the preparation method of the composite diaphragm in Example 1, except that: In step (1), the core reaction temperature is 83.2°C, the pressure is 2.1 MPa, the shell monomers acrylonitrile and 2-ethylhexyl acrylate are added in amounts of 9 parts and 36 parts, respectively, the reaction temperature is 75.3°C, and the pressure is 4.0 MPa; In step (2), the amount of boehmite added was 7.6 parts, and the stirring speed was 200 rpm; In step (3), the amounts of methyl methacrylate and ethyl acrylate added were 18 parts and 22 parts, respectively, the reaction temperature was 75.8°C, and the pressure was 2.9 MPa; In step (4), the amount of aluminum oxide added is 78 parts, and the amount of the emulsion containing the composite particles added is 90 parts; In step (6), the surface density of the first coating is 3.16 g / m 2 , the surface density of the second coating is 0.10g / m 2 .
[0099] Comparative Example 5 This comparative example refers to the preparation method of the composite diaphragm in Example 1, except that: In step (1), the core reaction temperature is 87.2°C, the pressure is 1.8 MPa, the shell monomers acrylonitrile and 2-ethylhexyl acrylate are added in amounts of 11 parts and 34 parts, respectively, the reaction temperature is 76.3°C, and the pressure is 4.2 MPa; In step (2), the amount of boehmite added was 5.8 parts, and the stirring speed was 120 rpm; In step (3), the amounts of methyl methacrylate and ethyl acrylate added were 21.5 parts and 18.5 parts, respectively, the reaction temperature was 76.4°C, and the pressure was 2.2 MPa; In step (4), the amount of aluminum oxide added is 83 parts, and the amount of the emulsion containing the composite particles added is 65 parts; In step (6), the surface density of the first coating is 1.6 g / m 2 , the surface density of the second coating is 0.15g / m 2 .
[0100] Comparative Example 6 This comparative example refers to the preparation method of the composite diaphragm in Example 1, except that: In step (1), the core reaction temperature is 84.8°C, the pressure is 2.4 MPa, the shell monomers acrylonitrile and 2-ethylhexyl acrylate are added in amounts of 13 parts and 32 parts, respectively, the reaction temperature is 77.3°C, and the pressure is 3.8 MPa; In step (2), the amount of boehmite added was 6.3 parts, and the stirring speed was 180 rpm; In step (3), the amounts of methyl methacrylate and ethyl acrylate added were 22 parts and 18 parts, respectively, the reaction temperature was 76.7°C, and the pressure was 2.3 MPa; In step (4), the amount of aluminum oxide added is 71 parts, and the amount of the emulsion containing composite particles added is 125 parts; In step (6), the surface density of the first coating is 3.16 g / m2 , the surface density of the second coating is 0.08g / m 2 .
[0101] Comparative Example 7 This comparative example refers to the preparation method of the composite diaphragm in Example 1, except that: In step (1), the core reaction temperature is 86.2°C, the pressure is 2.3 MPa, the shell monomers acrylonitrile and 2-ethylhexyl acrylate are added in amounts of 12 parts and 33 parts, respectively, the reaction temperature is 76.1°C, and the pressure is 4.2 MPa; In step (2), the amount of boehmite added was 6.8 parts, and the stirring speed was 175 rpm; In step (3), the amounts of methyl methacrylate and ethyl acrylate added were 20 parts and 20 parts respectively, the reaction temperature was 75.8°C, and the pressure was 2.9 MPa; In step (4), the amount of aluminum oxide added is 88 parts, and the amount of the emulsion containing composite particles added is 40 parts; In step (6), the surface density of the first coating is 1.62 g / m 2 The surface density of the second coating is 0.16g / m 2 .
[0102] Comparative Example 8 This comparative example refers to the preparation method of the composite diaphragm in Example 1, except that: In step (1), the core reaction temperature is 87.2°C, the pressure is 1.8 MPa, the shell monomers acrylonitrile and 2-ethylhexyl acrylate are added in amounts of 12 parts and 33 parts, respectively, the reaction temperature is 75.8°C, and the pressure is 4.1 MPa; In step (2), the amount of boehmite added was 4.2 parts, and the stirring speed was 180 rpm; In step (3), the amounts of methyl methacrylate and ethyl acrylate added were 20 parts and 20 parts respectively, the reaction temperature was 76.6°C, and the pressure was 2.3 MPa; In step (4), the amount of aluminum oxide added is 78 parts, and the amount of the emulsion containing the composite particles added is 90 parts; In step (6), the surface density of the first coating is 3.02 g / m 2 The surface density of the second coating is 0.16g / m 2 .
[0103] Comparative Example 9 This comparative example refers to the preparation method of the composite diaphragm in Example 1, except that: In step (1), the core reaction temperature is 84.6°C, the pressure is 2.2 MPa, the shell monomers acrylonitrile and 2-ethylhexyl acrylate are added in amounts of 11 parts and 34 parts, respectively, the reaction temperature is 73.9°C, and the pressure is 4.3 MPa; In step (2), the amount of boehmite added was 4.7 parts, and the stirring speed was 145 rpm; In step (3), the amounts of methyl methacrylate and ethyl acrylate added were 22 parts and 18 parts, respectively, the reaction temperature was 77.3°C, and the pressure was 2.5 MPa; In step (4), the amount of aluminum oxide added is 83 parts, and the amount of the emulsion containing the composite particles added is 65 parts; In step (6), the surface density of the first coating is 1.64 g / m 2 , the surface density of the second coating is 0.10g / m 2 .
[0104] Comparative Example 10 This comparative example refers to the preparation method of the composite diaphragm in Example 1, except that: In step (6), the first mixed slurry and the second mixed slurry are mixed together and coated in one step to obtain a composite diaphragm. The coating weight of the composite particles and the polymer particles remains unchanged, and the other conditions are the same as in Example 1.
[0105] Comparative Example 11 This comparative example refers to the preparation method of the composite diaphragm in Example 1, except that: In step (2), boehmite was not added, and the other conditions were the same as those in Example 1.
[0106] Experimental example 1. Test of glass transition temperature Tg, particle size, and ceramic ratio in composite particles (1) Tg test: The first polymer primary particle emulsion and the polymer particle emulsion in each embodiment and comparative example were dried separately, and 5-6 mg of each sample was weighed. The Tg was measured by differential scanning calorimetry using METTLER DSC3 testing equipment, a test temperature range of -80-200°C, and a heating rate of 6°C / min. After the test, the test curve was integrated to obtain the Tg of the test sample.
[0107] (2) Particle size test: The composite particle emulsion and polymer particle emulsion in each embodiment and comparative example were dropped into a Malvern 3000 to test the particle size. The test results showed a refractive index of 1.52, an absorptivity of 0.1, and a light shielding rate of 8% to 16%. The particle sizes D1 and D2 of the composite particles and polymer particles were obtained.
[0108] (3) Test of the proportion of ceramics in the composite particles: The composite particle emulsions in each embodiment and comparative example were dried, and the EDS of the dried powder was tested using a scanning electron microscope to obtain the proportion of the Al element, and the proportion of ceramics was estimated, and finally the proportion of ceramics in the first polymer was obtained.
[0109] The test results are shown in Table 1. Figure 4 is a Tg graph of the first polymer primary particles in Example 10 of the present invention; Figure 5 is a Tg diagram of the polymer particles in Example 10 of the present invention; Figure 6 This is the EDS graph of the composite particles in Example 10 of the present invention.
[0110] Table 1
[0111] 2. Composite diaphragm performance test (1) Air permeability growth rate test: Air permeability growth rate = (composite membrane air permeability - base membrane air permeability) / base membrane air permeability × 100%, where air permeability refers to the time required for 100 ml of gas to pass through a fixed area of the membrane.
[0112] (2) Thickness H of the filler layer in the first coating: Take a cross section of the composite diaphragm and test the cross section of the composite diaphragm using a scanning electron microscope to measure the thickness of the filler layer. Randomly test 5 points on the same sample and take the average value. Test 6 samples in parallel using the same method and take the final average value, which is the thickness of the filler layer.
[0113] (3) Composite particle embedding depth d and protrusion height h: Take a cross-section of the coated diaphragm and use a scanning electron microscope to test the depth of the composite particles embedded in the filler layer and the height of the protrusion from the second coating layer. Randomly test the depth of the composite particles embedded in the filler layer and the height of the protrusion from the second filler layer of 5 samples on the same sample and take the average value. Then test 10 samples in parallel using the same method and take the final average value, which is the depth d of the composite particles embedded in the filler layer and the height h of the protrusion from the second coating layer. (4) Polymer particle coverage test: Composite particle coverage η1: Take the cross section of the composite diaphragm, select 10 points, select the composite particles in the field of view at 2000 times, measure the maximum length of the composite particles along the coating surface direction, calculate the average value of the maximum length of all composite particles at the 10 points, test 5 samples in parallel in the same way, and finally take the average value L1 of the 5 samples; take the coated diaphragm to shoot an electron microscope, shoot 15 points at 3000 times (42.7μm×32.0μm), and count the number of composite particles at each point at this magnification, take the average number N1 of the 15 points, then the composite particle coverage η1=(N1×3.14×L1× L1) / (4×42.7×32.0), 5 samples are tested in parallel using the same method, and the average value of the final 5 samples is taken as the coverage rate of the composite particles; (When calculating the particle size of the composite particles, the present invention adopts a cross-sectional method to measure the maximum length of the composite particles parallel to the coating surface, which can better reflect the actual particle size of the composite particles distributed in the first coating layer. For example, when taking electron microscopy photos of the composite diaphragm surface to calculate the particle size of the composite particles, for those composite particles with more than half filled in the filler layer, the measured particle size is smaller than the actual one, which ultimately leads to a decrease in the calculated coverage rate of the composite particles, and a large error from the actual situation).
[0114] Polymer particle coverage η2: Take the coated diaphragm and take an electron microscope photo at 6 points at a magnification of 5000 (25.6μm×19.2μm), and count the number of polymer particles at each point at this magnification. The average value is taken as N2, and the coverage of the second polymer η2=(N2×3.14×D2×D2) / (4×25.6×19.2). Test 5 samples in parallel using the same method, and take the average value of the final 5 samples, which is the coverage of the polymer particles.
[0115] (5) Test for the ratio K of the number of polymer particles to the number of composite particles: From the test results of the above steps, it can be seen that the number of composite particles in each point (42.7μm×32.0μm) at a magnification of 3000 is N1, and the number of polymer particles in each point (25.6μm×19.2μm) at a magnification of 5000 is N2. Then K=(42.7×32×N2) / (25.6×19.2×N1)=2.78×N2 / N1. Five samples were tested in parallel using the same method, and the average value was finally taken, which is the ratio K of the second polymer to the number of composite particles.
[0116] (6) Composite diaphragm powder loss rate test: Use dye friction color fastness tester RT-300S for testing, take the composite diaphragm and cut it into 30cm×2cm long strip samples, weigh it, and fix the long strip sample with the coating surface facing up. Put lens paper on the friction piece and place it on the diaphragm. Start the power supply, rub the friction piece back and forth on the diaphragm 5 times, take out the diaphragm after friction, shake it lightly three times, and measure the mass of the diaphragm again. The difference between the two weights is divided by the total weight of the strip diaphragm coating to get the composite diaphragm powder loss rate.
[0117] (7) Test of adhesion strength with electrode sheet: The composite diaphragm and positive electrode sheet were cut into 4cm×6cm specifications. The coating surface of the electrode sheet (the coating composition is 95% LFP+2.5% PVDF+0.8% SP+1.6% CNT+0.1% plasticizer) corresponded to and overlapped with the coating surface of the diaphragm. After adjusting the parameters of the hot press (3MPa, 3mins, 90℃), dry pressing was performed. The adhesion strength between the diaphragm and the positive electrode sheet was tested by 180° peeling method, where the peeling speed was 60mm / min, and the adhesion strength between the coated diaphragm and the electrode sheet was obtained.
[0118] (8) Ionic conductivity performance: (In an argon glove box, the membrane was made into a 2016 button battery, and an appropriate amount of electrolyte (EC:PC:DEC = 1:3:5, 1.5 Mol / L LiPF6) was added. The AC impedance test in the electrochemical workstation was used to obtain σ = L / (Rb × A), where σ is the ionic conductivity (mS / cm); L is the thickness of the membrane (cm); Rb is the intrinsic resistance of the membrane (Ω); A is the effective area (cm 2 ).
[0119] (9) Thermal shrinkage performance: Take the composite diaphragm and cut a 100mm×50mm rectangular sheet along the MD direction of the composite diaphragm to test the length M1 and T1 of MD and TD. Clamp the sheet with two A4 papers and put it in a 130℃ oven for 30 minutes. Then test the length M2 and T2 of the diaphragm in MD and TD directions again. The thermal shrinkage values of the coated diaphragm in MD and TD directions are (M1-M2) / M1 and (T1-T2) / T1 respectively.
[0120] The test results of composite diaphragm performance are shown in Table 2. Figure 3 This is a surface SEM image of the composite diaphragm in Example 10 of the present invention.
[0121] Table 2
[0122] 3. Electrical performance test (1) Capacity retention rate test: The composite diaphragm and lithium iron phosphate positive electrode sheet and graphite negative electrode sheet are made into a battery cell by lamination process, and an appropriate amount of electrolyte (EC:PC:DEC=1:3:5, 1.5 mol / L LiPF6) is added. The battery is charged to 3.6V at a constant current of 1C, and then charged at a constant voltage of 3.6V to a current of 0.02C. The charge is terminated and the battery is allowed to stand for 30 minutes; the battery is discharged to 2.0V at a constant current of 1C, and the discharge is terminated and allowed to stand for 30 minutes. The first discharge capacity is recorded and the cycle is repeated for 300 times. The discharge capacity of the 300th cycle is recorded. The discharge capacity of the 300th cycle is divided by the discharge capacity of the first cycle, which is the capacity retention rate of the battery after 300 cycles.
[0123] (2) Lithium deposition in battery cells: Take the battery cells after 300 cycles of capacity retention test, disassemble them, and record the lithium deposition in the battery cells.
[0124] (3) Battery bulging: The composite diaphragm, lithium iron phosphate positive electrode sheet, and graphite negative electrode sheet are made into a battery cell using a stacking process. An appropriate amount of electrolyte (EC:PC:DEC=1:3:5, 1.5 mol / L LiPF6) is added. The overall thickness of the battery cell h1 is recorded. The battery cell is cycled at 0.2C for 200 cycles, and the thickness of the battery cell h2 after 200 cycles is recorded. The battery expansion coefficient is h2 / h1.
[0125] The test results are shown in Table 3.
[0126] Table 3
[0127] In Examples 1 to 10, all parameters were within the scope of the present invention, and the obtained composite separators showed good performance at both the separator level and the cell level.
[0128] When the proportion of ceramics in the composite particles is too low or there is no ceramic, the dispersibility and affinity between the composite particles and the filler are weakened, the composite particles are easily accumulated in the diaphragm, and the ion conduction channel of the composite particles is reduced, which can easily lead to lithium deposition in the battery cell. At the same time, the depth of the composite particles embedded in the ceramic is not enough, the adhesion between the composite particles and the ceramic is reduced, the diaphragm loses powder seriously, the composite particles fall off, affecting the adhesion between the diaphragm and the electrode, and the battery cell performance is reduced, such as Comparative Examples 1, 3 and 11.
[0129] If the particle size of the composite particles is too small, the coverage of the composite particles will increase at the same gram weight, the air permeability growth rate of the diaphragm will increase, the internal resistance will increase, and after the diaphragm and the electrode sheet are hot-pressed, the Gap point capacity provided by the composite particles will decrease, the liquid storage capacity of the battery cell will decrease, the battery cell expansion coefficient will increase, and the battery cell performance will decrease; if the particle size of the composite particles is too large, the coverage of the composite particles will decrease at the same gram weight, and the effective Gap site will decrease. When the diaphragm and the electrode sheet are hot-pressed, an effective Gap space cannot be provided, which will easily lead to an increase in the battery cell expansion coefficient. At the same time, if the particle size of the composite particles is too large, it will easily lead to the shedding of the composite particles, and the adhesion between the diaphragm and the electrode sheet will decrease, thereby affecting the overall battery cell performance, such as comparing 4 and 5; If the proportion of composite particles in the diaphragm is too high, the weight of the polymer particle coating will decrease, which will easily lead to a decrease in adhesion. At the same time, if the proportion of composite particles is too high, it will also easily lead to a larger air permeability growth rate of the diaphragm, and the composite particles will easily accumulate, resulting in lithium precipitation. If the proportion of composite particles is too low, the weight of the polymer particles will increase, the polymer particle coverage will increase, and the air permeability growth rate of the coated diaphragm will increase, affecting the internal resistance of the battery cell. When the proportion of composite particles is too low, the gap points provided will decrease, the battery cell expansion coefficient will increase, and the cycle performance will decrease, as shown in the comparison between 6 and 7. When the coating weight of the composite particles and the gram weight of the polymer particles increase at the same time, the overall coverage of the diaphragm increases, and the air permeability growth rate increases significantly, affecting the overall internal resistance of the battery cell and easily causing lithium deposition in the battery cell, thereby affecting the cycle performance of the battery cell; when the coating weight of the composite particles and the gram weight of the polymer particles decrease at the same time, the adhesion between the diaphragm and the electrode sheet decreases severely, the expansion rate of the battery cell increases, the internal resistance of the battery cell increases, and the cycle performance of the battery cell decreases, as shown in comparisons 8 and 9.
[0130] In Comparative Example 10, since most of the polymer particles are filled in the filler layer, the coverage measured by the test method of the polymer particle coverage of the present invention is much lower than the actual situation. Moreover, since most of the polymer particles are filled in the filler layer, the number of surface polymer particles is small, resulting in a significant decrease in adhesion and heat resistance.
[0131] Although the present invention has been illustrated and described using specific embodiments, it should be appreciated that the above embodiments are merely intended to illustrate the technical solutions of the present invention rather than to limit them. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents, without departing from the spirit and scope of the present invention. However, these modifications or replacements do not deviate from the essence of the corresponding technical solutions within the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.
Claims
1. A composite diaphragm, characterized in that: The invention comprises a base film and a coating layer provided on at least one surface of the base film; the coating layer comprises a first coating layer provided on the surface of the base film and a second coating layer provided on at least a part of the surface of the first coating layer; The first coating layer includes filler particles and composite particles, the filler particles are accumulated to form a filler layer, the composite particles are embedded in the filler layer and form protrusions on the surface of the filler layer; the composite particles include secondary particles formed by the co-agglomeration of first polymer primary particles and ceramics; The second coating layer comprises polymer particles; the polymer particles comprise second polymer primary particles; The height h of the composite particles protruding from the second coating layer satisfies 1 μm≤h≤4.9 μm; The coverage rate η1 of the composite particles relative to the base film is 4.2%~18.8%, the coverage rate η2 of the polymer particles relative to the base film is 12.5%~31.7%, and the total coverage rate η of the composite particles and the polymer particles relative to the base film is 25.0%~40.0%.
2. The composite diaphragm according to claim 1, characterized in that The thickness of the filler layer is H, and the depth to which the composite particles are embedded in the filler layer is d, satisfying the following: 1 μm≤H≤2 μm, H / 2≤d≤H.
3. The composite diaphragm according to claim 1, characterized in that The surface density of the composite particles is X, and the surface density of the polymer particles is Y, which satisfies: 0.20 g / m 2 ≤X≤0.60g / m 2 , Y=-0.125X+a, 0.15≤a≤0.2; And / or, the ratio K of the number of the polymer particles to the number of the composite particles satisfies: 11<K<750.
4. The composite diaphragm according to claim 1, characterized in that Meet at least one of the following characteristics: (1) The particle size of the composite particles is 4 to 6 μm, and / or the particle size of the first polymer primary particles is 0.4 to 0.6 μm, and / or the particle size of the ceramic is 0.4 to 0.6 μm; (2) In the composite particles, the ceramic accounts for 5% to 12% by mass; (3) The ceramic includes at least one of boehmite, alumina, silica, zirconia, LATP, and LLZO; (4) The ceramic forming the composite particles is a coupling agent-modified ceramic; (5) The glass transition temperature Tg of the first polymer primary particles is -5 to 5°C; (6) The first polymer primary particle comprises a core and a shell coated on the surface of the core; the core monomer forming the core and the shell monomer forming the shell are independently selected from at least one of methacrylonitrile, styrene, acrylonitrile, ethyl acrylate, 1-butene, 2-ethylhexyl acrylate, isooctyl acrylate, and n-butyl acrylate; and the shell monomers contain at least one monomer different from the core monomer; (7) The particle size of the polymer particles is 0.6-1.0 μm; (8) The glass transition temperature Tg of the polymer particles is 45-55°C; (9) The monomers forming the polymer particles include any two of methyl methacrylate, butyl methacrylate, ethyl acrylate, isooctyl acrylate, and n-butyl acrylate.
5. The composite diaphragm according to claim 1, characterized in that Meet at least one of the following characteristics: (1) The mass proportion of the composite particles in the total coating is 11.5% to 18.5%; (2) The mass proportion of the polymer particles in the total coating is 3.0% to 9.0%; (3) The filler particles account for 66% to 86% of the total coating mass; (4) The filler particles include one or more of inorganic oxides, inorganic hydroxides, metal salts or organic non-polymer particles; (5) The particle size of the filler particles is 0.5-0.8 μm; (6) More than 95% of the second coating layer is located on the surface of the filler layer; (7) The first coating layer further contains a first binder, and the mass proportion of the first binder in the total coating layer is 2% to 8%; and / or the second coating layer further contains a second binder, and the mass proportion of the second binder in the total coating layer is 0.05% to 0.50%; (8) The first coating layer further comprises a first wetting agent, and the mass proportion of the first wetting agent in the total coating layer is 0.1% to 1.0%; and / or, the second coating layer further comprises a second wetting agent, and the mass proportion of the second wetting agent in the total coating layer is 0.02% to 0.2%.
6. The method for preparing the composite diaphragm according to any one of claims 1 to 5, characterized in that: The following steps are involved: Mixing first raw materials to obtain a first mixed slurry, wherein the first raw materials include filler particles and an emulsion containing composite particles; mixing a second raw material to obtain a second mixed slurry, wherein the second raw material includes an emulsion containing polymer particles; The first mixed slurry is applied on at least one side of the base film and dried to obtain a first coating layer; the second mixed slurry is applied on the first coating layer and dried to obtain the composite diaphragm.
7. The method for preparing a composite diaphragm according to claim 6, characterized in that: The preparation method of the emulsion containing composite particles comprises the following steps: S1. A first emulsifier, a core monomer, and a first initiator are subjected to a first polymerization reaction in a first solvent to obtain a core particle emulsion; the core particle emulsion is subjected to UV irradiation, a shell monomer and a second initiator are added to perform a second polymerization reaction to obtain an emulsion containing a first polymer primary particle; S2. Modifying the surface of the ceramic by reacting the ceramic with a coupling agent, and then adding the emulsion containing the first polymer primary particles and salt and stirring to obtain the emulsion containing the composite particles.
8. The method for preparing a composite diaphragm according to claim 6 or 7, characterized in that: The preparation method of the emulsion containing polymer particles comprises the following steps: The second emulsifier, the monomer for forming the second polymer and the third initiator are subjected to a third polymerization reaction in the second solvent to obtain the emulsion containing the polymer particles.
9. A secondary battery, characterized in that: The invention relates to a composite diaphragm according to any one of claims 1 to 5, or a composite diaphragm prepared by the method for preparing the composite diaphragm according to any one of claims 6 to 8.
Citation Information
Patent Citations
Adhesive diaphragm and preparation method thereof
CN114665226A
Secondary battery diaphragm and secondary battery
CN118712658A
Secondary battery, battery module, battery pack, and electric device
CN119994384A
Low-temperature high-adhesion heat-resistant diaphragm
CN219801204U
A porous separator with water-based organic / inorganic complex coating, a method for preparing the same and an electrochemical device using the same
KR101341196B1
Cited By
Composite diaphragm as well as preparation method and application thereof
CN121484383A